Resource use efficiency and economics of marketing of green chilli - K P Kulkarni, P P Jagtap, U S Shingane (Journal of Spices and Aromatic Crops, 2014)
The study was conducted in Achalpur tahsil of Amravati district of Maharashtra with a sample of 80 farmers selected randomly from four villages with twenty farmers from each village. Data used were pertaining to the period 2009–10. Production function analysis of data indicated that, among various resources selected, human labour, bullock labour and machine power in small farmers, seed, bullock labour and fertilizers and manures in medium farmers and the fertilizers and manures in large farmers were statistically significant. The ratio of marginal value product to its acquisition cost per unit was found to be greater than unity for the variables plant protection chemicals and fertilizers and manures in small farmers, variables human labour and fertilizers and manures in medium farmers and the variables seed, human labour and fertilizers and manures in large farmers. Also economic analysis of data indicated that majority of farm produce was routed through two marketing channels, Channel-I (Producer-commission agent-retailerconsumer) and Channel-II (Producer-commission agent-Wholesaler-retailer-consumer). Producer’s share in consumer’s rupee was found to be 56.31%, 40.59% and price spread was Rs. 655.35 Rs. 891 q-1 for Channel-I and Channel-II respectively.